1990
DOI: 10.1080/07391102.1990.10507831
|View full text |Cite
|
Sign up to set email alerts
|

Organic Osmotic Effectors and Chromatin Structure

Abstract: Organic amino compounds (taurine, glycine) and polyols (mannitol, sorbitol) are used as osmotic effectors by most animal cells, particularly by some marine invertebrates, but also to a limit extent by mammalian cells. Using physico-chemical techniques (circular dichroism, thermal denaturation, solubility, electrophoresis and electric linear dichroism), we demonstrated that some of these effectors prevent chromatin aggregation, without histone release. The influence of glycine on chromatin aggregation, dissocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Previous studies (Buche et al, 1989(Buche et al, , 1990(Buche et al, , 1993 have confirmed this protection effect. Indeed, these compounds hinder chromatin precipitation induced by NaCl, KCI, CaCl2, or MgCl2 in vitro.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Previous studies (Buche et al, 1989(Buche et al, , 1990(Buche et al, , 1993 have confirmed this protection effect. Indeed, these compounds hinder chromatin precipitation induced by NaCl, KCI, CaCl2, or MgCl2 in vitro.…”
Section: Introductionsupporting
confidence: 68%
“…Reaching a sufficient level of phosphate charges neutralization to produce DNA precipitation thus requires a greater amount of cationic compound. This also explains the effects of glycine and taurine in the chromatin precipitation experiments of Buche et al (1989Buche et al ( , 1990Buche et al ( , 1993 and probably their presence in the euryhaline cells that are able to support osmotic stress.…”
Section: Resultsmentioning
confidence: 71%
“…Organic osmolytes stabilize proteins, counteracting the adverse effects of inorganic and organic ions [1,7,8,10,12,22,38,39]. Possibly, destabilization of proteins participates in the disintegration of apoptotic cells.…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, the stability of chromosomal sized DNA may suffer from replacement of histones by inorganic cations leading to an increased frequency of DNA dsb. These effects of inorganic ions are offset by accumulation of compatible organic osmolytes, which are more compatible with chromatin structure (33).…”
Section: Discussionmentioning
confidence: 99%